The Balance of Life Quality among the Elderly through the Practice of Sunnah Nabawiyyah: A Study at Madrasah Ibnu Mas'ud, Malaysia - Maisarah Saidin; Latifah Abdul Majid (Human Resources Management Academic Research Society (HRMARS), 2026)
Indexed by ERA